Pyogenic Discitis in Female after Delivery and Pelvic Surgery - Shalal, Maad M; Al-Mukhtar, Sadiq A. (AL-Kindy College Medical Journal, 2007)
Background: Pyogenic discitis most frequently occursafter home delivery, hemorridectomy, and dilatation andcurettage. Discitis is generally due to blood borne bacterialinvasion of the disc from adjacent end-plate viacommunicating vessels. Infective discitis remains anuncommon, but potentially serious cause for back pain.Delayed diagnosis can occur and a high index of suspicionmay occur.Methods: The study included 30 patients suffering fromlocalized low back pain with limitation of movement.Diagnosis was made by history, physical examination andinvestigation mainly E.S.R and MRI.Results: 50.3% of patient with discitis had a history ofvaginal delivery, 15% had a history of hemorridectomy and10% had a history of dilatation and curettage and cesareansection surgery. All patients had elevated E.S.R, PositiveC-reactive protein and positive MRI finding.Conclusion, We must think of Pyogenic discitis in anypatient with sever backache, fever, local tenderness, andhigh ESR